PELESTARIAN GHUMAH BAGHI (RUMAH TRADISIONAL BERBAHAN DASAR KAYU) DI KELURAHAN PELANG KENIDAI, KOTA PAGARALAM - Oktarine Melly Aminah Harum; Indra Gumay Febryano; Christine Wulandari; Wahyu Hidayat (Jurnal Hutan Tropis, 2019)
The existence of traditional house that are made of wood is very closely related to the preservat ion of the culture that develops in the community. The purpose of this research is to elucidate the factors that may have influenced the community to maintain their traditional wooden houses. This study used a qualitative approach with case study method. Data collection was conducted by in-depth interviews, participant observation, and documentation studies. The data obtained were then analysed to elaborate on the factors that may have influenced the community to maintain their traditional wooden-based houses which are commonly called ghumah baghi. The results of the study show that culture, inheritance, raw materials, economic conditions of the community, knowledge of the community, and government policies are the factors that may have encouraged the community to maintain the existence of their ghumah baghi.Involving the various related stakeholders, the government policy in protecting ghumah baghi as a cultural sanctuary, and the cultivation of substitute wood species as raw material for making ghumah baghi, are all essential endeavours in its conservation.